Evaluation Criteria That Have Been Applied for Education Standardization Among Research Assistants in Forensic Medicine in Dokuz Eylul University Faculty of Medicine a Model Study - Özdemir, Mehmet Hakan; Salaçin, Serpil (The Bulletin of Legal Medicine, 2002)
Changing information and application methods due to technologic progression in the whole world have emerged new approaches for education models as in every area. In this paper, “Education Evaluation Criteria” have been explained that is a part of education model prepared by Forensic Medicine Department for research assistants in medicine. These criteria have been assessed according to “Apphcation and Evaluation Regulation for Specialist and Fellowship Education in Medicine” prepared by Deanship of Dokuz Eylül University Faculty of Medicine. Key Words: Forensic medicine, education